Facilitating with Stories - Rixon, Andrew,Lloyd, Cathryn (Cambridge Scholars Publishing, 2023)
This book provides a rich connection between theory and practice for those seeking to work with stories in organisational, community, educative or coaching settings. With an international cast of contributors, it charters a unique inquiry into both ethics and the facilitation philosophies for working with stories supporting educators, facilitators, trainers and consultants towards more effective and considered practice. This book will be a valuable resource for professionals and reflective practitioners seeking to explore: What informs an ethics of facilitating with stories? How can we create safe spaces for story work? In what ways do we need to be attuned to power when working with stories in organisations and corporations? What are the unintended and ethical consequences of facilitating with stories?
9781527521001
Keywords: Ethik; Moralphilosophie; Literaturwissenschaft; Wirtschaftswissenschaften: Allgemeines; Pädagogik; Language and Linguistics; Business; Management Information Systems